2011
DOI: 10.1075/ijcl.16.4.02har
|View full text |Cite
|
Sign up to set email alerts
|

A genre, collocational, and constructional analysis of RISK

Abstract: Scholars of language have begun to explore the popular academic topic that is "risk" and to establish the viability of corpus linguistics for such analysis. We extend existing scholarship by analyzing the noun lemma RISK over the last two decades of contemporary American discourse with recourse to the Corpus of Contemporary American English. Using the corpus procedures of frequency analysis, concordance contextual analysis, collocational analysis, and a variation on distinctive-collexeme analysis, we revisit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Of these the specification of an unwanted event is most common. Often, such events are health related, for example, cancer , heart disease , Alzheimer's [disease], diabetes , developing allergies , illnesses , and injury . In the case of safety and security , what is represented by prepositional phrase complements is typically an asset at stake, for example, safety of their children and security of the troops .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these the specification of an unwanted event is most common. Often, such events are health related, for example, cancer , heart disease , Alzheimer's [disease], diabetes , developing allergies , illnesses , and injury . In the case of safety and security , what is represented by prepositional phrase complements is typically an asset at stake, for example, safety of their children and security of the troops .…”
Section: Resultsmentioning
confidence: 99%
“…In corpus linguistics, collocation patterns have received special attention. For example, collocation analyses of risk have identified a strong orientation towards medicine and health among its lexical associates …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we manually perused some of the tokens in context, a practice also known as 'concordance contextual analysis' (Hardy & Colombini 2011). This practice is necessary in BP studies because sometimes synonyms in the same context with the same distributions may have different meanings, as has been shown in studies by Liu (2010), and because sometimes the information needed is not accessible via a machine query.…”
Section: Corpus Query and Analysis Proceduresmentioning
confidence: 99%
“…By using COCA, it was found that risk was frequently mentioned in the academic text comparing to fiction, newspaper, spoken and magazine (Hardy & Colombini, 2011). According to Hardy and Colombini (2011), to find the positive prosody of risk was exceedingly difficult, but they still found it such as "…those risks are worth taking." Tang and Rundblad (2015) investigated how media report materials in drinking water that could potentially harm human health through Wordsmith software.…”
mentioning
confidence: 99%
“…A study conducted by Hardy and Colombini (2011) also investigated the positive prosody of risk through frequency analysis, concordance contextual analysis, collocational analysis and a variation of on distinctive-collexem analysis, since some previous studies mostly have shown the negative prosody and medical result of the word risk. By using COCA, it was found that risk was frequently mentioned in the academic text comparing to fiction, newspaper, spoken and magazine (Hardy & Colombini, 2011).…”
mentioning
confidence: 99%